Community stance towards sloth bear (Melursus ursinus) conservation in Odisha, India - PRAKASH C. MARDARAJ; TARA J. PIRIE; JANMEJAY SETHY; SATYARANJAN BEHERA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Mardaraj PC, Pirie TJ, Sethy J, Behera S. 2023. Community stance towards sloth bear (Melursus ursinus) conservation in Odisha, India. Biodiversitas 24: 2521-2526. The human dimension is an essential component of extensive carnivore management and conservation. People living in bear habitats often fear encounters with these animals, and negative interactions can significantly affect people's livelihoods, attitudes, and tolerance toward the conservation initiatives of bears. To investigate the effect of such interactions on people's attitudes and livelihoods, we surveyed 510 households through semi-structured interviews located around five reserve forests of the Nilgiri wildlife range in a coastal district of Odisha, India. Gender, education, dependency on the forest, and specifics of bear encounters were the parameters taken to know the villagers' attitudes toward bear conservation. The average age of respondents was 46 (17-88) years; 78.8% (n= 402) were male. There are 37.5% of the respondents below the poverty level with annual incomes less than $ 514 USD. The majority of respondents, 85%, showed favorable opinions regarding sloth bears (Melursus ursinus Shaw, 1791), with only 15% expressing a negative perception. Bears were encountered by 87% of the total participants, with 45% encountering a sloth bear weekly. The study identified that 82.9% of villagers were more likely to state sloth bears were problematic rest disagreed with it. The educated interviewer was strongly supporting bear conservation in that landscape. The perspectives of the villagers and their experiences on their adverse feeling toward the bears need to minimize through suggested participatory and community-based mitigation strategies for long time conservation of the sloth bear in the landscape.